Coral conservation requires ecological climate‐change vulnerability assessments. Issue 4 (8th February 2021) - Dixon, Adele M; Forster, Piers M; Beger, Maria
Abstract : Climate‐driven changes to environmental conditions are driving severe declines of coral reef ecosystems. Current climate vulnerability estimates commonly focus on ocean warming and typically overlook ecological responses or use broad proxies to represent responses, leading to management decisions based on incomplete views of coral reef futures. We explore four underdeveloped aspects of climate vulnerability assessments and make the following recommendations: (1) use climate projections based on changes in global warming as future scenarios in place of the more common emissions scenarios; (2) include available high‐resolution projections for climate variables in addition to thermal stress; (3) combine projected climate stressors accounting for uncertainty in future outcomes; and (4) quantitatively assess historical and project future ecological sensitivity and adaptive capacity of corals to multiple stressors. We demonstrate how this framework can be used to reduce uncertainty in projected climate vulnerability and facilitate targeted investment in managing reefs most likely to endure climatic disturbances.